As Condições socioambientais como potenciais riscos à saúde dos camponeses do assentamento Companheiro Keno, município de Jacarezinho/PR - Flausino, Camila Isabel Ruivo Jorge Ribeiro [UNESP] (2019)
The process of production of the Brazilian countryside has historically been characterized by the agro-export monoculture, added in the last four decades by the intense mechanization and the excessive consumption of the technological agrochemical package, with emphasis on the poisons and fertilizers. The indiscriminate use of these pesticides, as well as exposure to bad weather and the practice of some activities without personal protective equipment (PPE), can create risks to the health of the worker, such as cancer, neurological problems, infertility, among others. Therefore, the focus of this study was to identify the most common causes of accidents / illnesses in the activities of rural workers, daily habits in agricultural practices, as well as socioenvironmental conditions as potential health risks for rural peasants in the Keno Township, municipality of Jacarezinho / PR. For that, a semi-structured questionnaire was developed and applied, with general and specific questions about work safety practices and, mainly, the use of pesticides and possible associated pathologies, together with 54 settled families. In addition, it will refer to INCA, ABRASCO, DataSUS, SINITOX, among others, databases for the sizing of the abovementioned problems. The results showed that; workers suffer from the excessive physical demands of work, and osteo muscular diseases are the ones that most affect workers, the prevention measures adopted are limited to the use of only some of the indicated PPE, such as boots and gloves due to lack of access, but without orientation of use, and other health protection measures revolve around guidelines on work forms and rest breaks. The analysis of the results showed that most of the settlers do not have access to the agronomic prescription...